Problem-Solving Ability Based on Math Anxiety in Senior High School Students During the Computer-Based Written Exam - Syipa Lisfianisa; Aan Hasanah (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
Mathematical problem-solving is a crucial competency in high school education, but students often face challenges due to psychological factors such as math anxiety. This study aimed to analyze students' mathematical problem-solving abilities based on their level of math anxiety. This research used a qualitative descriptive approach. The subjects were 32 students of class XII SMAN 17 Bandung. Three students were selected as primary subjects based on high, medium, and low levels of mathematical anxiety. Data were collected through math anxiety questionnaires, written tests (containing 2 UTBK questions from 2020 and 2024), and interviews. The findings showed that the student with low math anxiety performed well in all four problem-solving stages, while the student with moderate anxiety showed partial success, particularly struggling in the review phase. The student with high anxiety showed poor performance across all stages due to emotional barriers such as fear, nervousness, and lack of concentration. Math anxiety significantly influences students' mathematical problem-solving skills, there is a negative relationship between the level of mathematical anxiety and students’ problem-solving abilities. Students with lower anxiety are better able to understand, plan, and solve problems effectively. These findings highlight the importance of addressing emotional factors in math education and suggest the need for anxiety-reducing strategies in the classroom.